Corrosion-resistant insulating material for street code protective sleeve and preparation method of corrosion-resistant insulating material

By generating calcium oxide on carbon fiber surfaces and forming covalent bonds with an organic copolymer, the corrosion-resistant insulating material addresses insulation and corrosion challenges, offering improved mechanical properties and durability for street code protective covers.

CN119161675AInactive Publication Date: 2024-12-20GUANGDONG DIANAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411285888.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Street code protective covers face challenges in maintaining excellent insulation and corrosion resistance due to exposure to extreme weather and chemical corrosive media, with existing materials lacking sufficient durability and longevity.

Method used

A corrosion-resistant insulating material is developed by generating calcium oxide on carbon fiber surfaces, modifying it with a silane coupling agent, and grafting it with 5-fluorosalicylaldehyde to form covalent bonds with an organic copolymer, enhancing compatibility and dispersibility, and incorporating specific components like PVC, ABS, and low-density polyethylene for improved mechanical properties and corrosion resistance.

Benefits of technology

The material exhibits enhanced mechanical properties and corrosion resistance, with reduced self-agglomeration and improved compatibility, extending the service life of street code protective covers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant insulating material for a street code protective sleeve and a preparation method of the corrosion-resistant insulating material, and belongs to the technical field of street code protective sleeve materials. The corrosion-resistant insulating material is prepared from the following components: 70 to 80 parts of PVC (Polyvinyl Chloride), 20 to 30 parts of ABS (Acrylonitrile Butadiene Styrene), 10 to 12 parts of low-density polyethylene, 18 to 24 parts of modified filler, 3 to 5 parts of stabilizer, 2 to 3 parts of lubricant, 1.0 to 1.5 parts of antioxidant and 0.6 to 1.0 part of light stabilizer. Calcium oxide is generated on the surface of the carbon fiber, and then surface modification is performed through a silane coupling agent, so that the carbon fiber can be grafted with fluorosalicylaldehyde and can also form covalent bond connection with an organic copolymer, and the compatibility and dispersity of carbon fiber / calcium oxide mixed particles in a system are further improved; the mechanical property and the corrosion resistance of the corrosion-resistant insulating material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of street code protection cover materials, and relates to a corrosion-resistant insulating material for a street code protection cover and a preparation method thereof. Background Art

[0002] As an indispensable part of the power system, the street code must have excellent insulation performance to ensure the safe and stable operation of the entire power system. In addition, since street codes are usually installed outdoors in extreme weather and chemical corrosion environments, they will inevitably face the threat of various corrosive media, such as acid rain, salt spray, and erosion by various chemicals. Protective covers are usually made of high-performance materials, such as high molecular polymers or other special coatings. These materials not only have excellent insulation properties, but also can resist the influence of natural factors such as ultraviolet rays, temperature changes and humidity fluctuations. In this case, the corrosion-resistant insulating protective cover is particularly important. It can effectively protect the street code from these corrosive media, thereby significantly improving the weather resistance and corrosion resistance of the material, thereby extending the service life of the street code.

[0003] Carbon fiber is mainly composed of carbon elements and has the characteristics of high temperature resistance, friction resistance, thermal conductivity and corrosion resistance. Its main use is as a reinforcing material combined with resin, metal, ceramic and carbon to manufacture advanced composite materials. Carbon fiber can improve the strength and durability of sheath materials due to its excellent mechanical properties, corrosion resistance and high temperature performance. However, the corrosion resistance of carbon fiber composites may be affected by the matrix resin and interface. The bonding force between carbon fiber and matrix can be improved by surface treatment, reinforcement layer coating and other methods. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant insulating material for street code protective cover and a preparation method thereof. The present invention generates calcium oxide on the surface of carbon fiber, and then performs surface modification through a silane coupling agent so that it can be grafted with 5-fluorosalicylaldehyde and can also form a covalent bond with an organic copolymer, thereby further improving the compatibility and dispersibility of carbon fiber / calcium oxide mixed particles in the system, and improving the mechanical properties and corrosion resistance of the corrosion-resistant insulating material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A corrosion-resistant insulating material for a street code protective cover comprises the following components by weight: 70-80 parts of PVC, 20-30 parts of ABS, 10-12 parts of low-density polyethylene, 18-24 parts of modified filler, 3-5 parts of stabilizer, 2-3 parts of lubricant, 1.0-1.5 parts of antioxidant and 0.6-1.0 parts of light stabilizer.

[0007] As a preferred technical solution of the present invention, the stabilizer is one or more of zinc stearate, magnesium stearate and triphenyl phosphate.

[0008] As a preferred technical solution of the present invention, the lubricant is one or more of stearic acid, polyethylene wax, glycerol stearate and OPE wax.

[0009] As a preferred technical solution of the present invention, the antioxidant is one or more of antioxidant 1076, antioxidant 626, antioxidant 168 and antioxidant 1010.

[0010] As a preferred technical solution of the present invention, the low-density polyethylene is Dow low-density polyethylene LDPE-740E.

[0011] As a preferred technical solution of the present invention, the light stabilizer is one or more of the ultraviolet absorber UV-326, the ultraviolet absorber UV-327 and the ultraviolet absorber UV-1130.

[0012] The present invention discloses a method for preparing the modified filler, comprising the following steps:

[0013] S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles;

[0014] S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles;

[0015] S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

[0016] As a preferred technical solution of the present invention, in step S1, the soaking condition is soaking at a temperature of 40-45°C for 3.0-4.0h.

[0017] As a preferred technical solution of the present invention, in step S1, the stirring and mixing is stirring at a rotation speed of 200-300 r / min for 20-30 min.

[0018] As a preferred technical solution of the present invention, in step S1, the washing is performed by washing with deionized water until it becomes neutral.

[0019] As a preferred technical solution of the present invention, in step S1, the drying is performed at a temperature of 110-120° C. for 3-4 hours.

[0020] As a preferred technical solution of the present invention, in step S1, the calcination is performed at a temperature of 600-800°C for 2-3h.

[0021] As a preferred technical solution of the present invention, in step S1, the mass ratio of the carbon fiber, the sodium hydroxide aqueous solution, the calcium chloride and the deionized water is 3.0-3.6:8-10:1.5-1.8:40-60.

[0022] As a preferred technical solution of the present invention, in step S1, the mass fraction of the sodium hydroxide aqueous solution is 20%.

[0023] As a preferred technical solution of the present invention, in step S1, the mass fraction of the ammonia water is 25-30%; the amount of ammonia water added is until no precipitation is generated.

[0024] As a preferred technical solution of the present invention, in step S2, the stirring and dispersing is stirring at a rotation speed of 500-600 r / min for 30-45 min.

[0025] As a preferred technical solution of the present invention, in step S2, the heating and stirring is stirring at a temperature of 40-60°C for 3-4h.

[0026] As a preferred technical solution of the present invention, in step S2, the continued stirring is stirring at a temperature of 60-70°C for 5-6h; and the drying is drying at a temperature of 80°C to constant weight.

[0027] As a preferred technical solution of the present invention, in step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 5-8:35-40:1.3-1.6:20-25.

[0028] As a preferred technical solution of the present invention, in step S2, the silane coupling agent is silane coupling agent NQ-62, which contains active amino groups and carbon-carbon double bonds, and can not only react chemically with 5-fluorosalicylaldehyde, but also form covalent bonds with organic copolymers, and can greatly increase the interfacial bonding strength between the carbon fiber / calcium oxide mixed particles and other components in the PVC / ABS system.

[0029] As a preferred technical solution of the present invention, in step S2, the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.45-0.48:4.0-4.5.

[0030] As a preferred technical solution of the present invention, in step S3, the melt extrusion is carried out at a screw speed of 50-60 r / min and a temperature of 180-200°C.

[0031] As a preferred technical solution of the present invention, in step S3, the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 8-9:10-14:0.40-0.43.

[0032] As a preferred technical solution of the present invention, in step S3, the organic copolymer is styrene-glycidyl methacrylate copolymer.

[0033] The invention discloses a method for preparing a corrosion-resistant insulating material for a street code protective cover, the preparation method comprising the following steps:

[0034] Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix;

[0035] Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

[0036] As a preferred technical solution of the present invention, in step one, the stirring and mixing is mixing at a temperature of 120-135°C and a rotation speed of 600-700 r / min for 20-30 min; the continued mixing is mixing at a temperature of 120-135°C and a rotation speed of 1000-1200 r / min for 20-30 min.

[0037] As a preferred technical solution of the present invention, in step 2, the melt extrusion is carried out at a screw speed of 50-58 r / min and a temperature of 190-200°C.

[0038] Beneficial effects of the present invention:

[0039] The present invention generates calcium oxide on the surface of carbon fiber, and then performs surface modification through a silane coupling agent, so that 5-fluorosalicylaldehyde can be grafted and covalently bonded with an organic copolymer, thereby further improving the compatibility and dispersibility of carbon fiber / calcium oxide mixed particles in the system and improving the mechanical properties and corrosion resistance of the corrosion-resistant insulating material. DETAILED DESCRIPTION

[0040] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0041] Example 1

[0042] A corrosion-resistant insulating material for a street code protective cover comprises the following components in parts by weight: 70 parts of PVC, 20 parts of ABS, 10 parts of low-density polyethylene, 18 parts of modified fillers, 3 parts of stabilizers, 2 parts of lubricants, 1.0 parts of antioxidants and 0.6 parts of light stabilizers; the low-density polyethylene is Dow low-density polyethylene LDPE-740E; the stabilizer is formed by mixing zinc stearate and triphenyl phosphate in a mass ratio of 1:2.5; the lubricant is formed by mixing stearic acid and OPE wax in a mass ratio of 1:1; the antioxidant is formed by mixing antioxidant 1076, antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2:1.6; the light stabilizer is an ultraviolet absorber UV-326.

[0043] Wherein, the preparation method of the modified filler comprises the following steps:

[0044] S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles;

[0045] S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles;

[0046] S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

[0047] In step S1, the soaking condition is soaking at 40°C for 3.0 hours; the stirring and mixing is stirring at a speed of 200r / min for 20 minutes; the washing is washing with deionized water until neutral; the drying is drying at 110°C for 3 hours; the calcination is calcining at 600°C for 2 hours; the mass ratio of the carbon fiber, sodium hydroxide aqueous solution, calcium chloride and deionized water is 3.0:8:1.5:40; the mass fraction of the ammonia water is 25%; the amount of ammonia water added is until no precipitation is generated;

[0048] In step S2, the stirring and dispersing is stirring at a speed of 500 r / min for 30 minutes; the heating and stirring is stirring at a temperature of 40°C for 3 hours; the continued stirring is stirring at a temperature of 60°C for 5 hours; the drying is drying at a temperature of 80°C to constant weight; in step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 5:35:1.3:20; the silane coupling agent is silane coupling agent NQ-62; the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.45:4.0.

[0049] In step S3, the melt extrusion is carried out at a screw speed of 50 r / min and a temperature of 180° C.; the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 8:10:0.40; and the organic copolymer is styrene-glycidyl methacrylate copolymer.

[0050] A method for preparing a corrosion-resistant insulating material for a street code protective cover, the preparation method comprising the following steps:

[0051] Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix;

[0052] Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

[0053] In step 1, the stirring and mixing is mixing at a temperature of 120° C. and a speed of 600 r / min for 20 min; the continued mixing is mixing at a temperature of 120° C. and a speed of 1000 r / min for 20 min;

[0054] In step 2, the melt extrusion is performed at a screw speed of 50 r / min and a temperature of 190° C.

[0055] Example 2

[0056] A corrosion-resistant insulating material for a street code protective cover comprises the following components in parts by weight: 75 parts of PVC, 25 parts of ABS, 10.5 parts of low-density polyethylene, 20 parts of modified fillers, 3.5 parts of stabilizers, 2.5 parts of lubricants, 1.2 parts of antioxidants and 0.5 parts of light stabilizers; the low-density polyethylene is Dow low-density polyethylene LDPE-740E; the stabilizer is formed by mixing zinc stearate and triphenyl phosphate in a mass ratio of 1:2.5; the lubricant is formed by mixing stearic acid and OPE wax in a mass ratio of 1:1; the antioxidant is formed by mixing antioxidant 1076, antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2:1.6; the light stabilizer is an ultraviolet absorber UV-326.

[0057] Wherein, the preparation method of the modified filler comprises the following steps:

[0058] S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles;

[0059] S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles;

[0060] S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

[0061] In step S1, the soaking condition is soaking at 42°C for 3.5 hours; the stirring and mixing is stirring at a speed of 230r / min for 25 minutes; the washing is washing with deionized water until neutral; the drying is drying at 113°C for 3.3 hours; the calcination is calcining at 667°C for 2.3 hours; the mass ratio of the carbon fiber, sodium hydroxide aqueous solution, calcium chloride and deionized water is 3.2:8.7:1.6:47; the mass fraction of the ammonia water is 27%; the amount of ammonia water added is until no precipitation is produced;

[0062] In step S2, the stirring and dispersing is stirring at a speed of 530 r / min for 35 minutes; the heating and stirring is stirring at a temperature of 47° C. for 3.5 hours; the continued stirring is stirring at a temperature of 65° C. for 5.5 hours; the drying is drying at a temperature of 80° C. to constant weight; in step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 6:37:1.4:22; the silane coupling agent is silane coupling agent NQ-62; the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.46:4.2.

[0063] In step S3, the melt extrusion is carried out at a screw speed of 55 r / min and a temperature of 185°C; the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 8.3:11:0.41; and the organic copolymer is styrene-glycidyl methacrylate copolymer.

[0064] A method for preparing a corrosion-resistant insulating material for a street code protective cover, the preparation method comprising the following steps:

[0065] Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix;

[0066] Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

[0067] In step 1, the stirring and mixing is performed at a temperature of 125° C. and a speed of 630 r / min for 25 min; the continued mixing is performed at a temperature of 125° C. and a speed of 1060 r / min for 25 min;

[0068] In step 2, the melt extrusion is carried out at a screw speed of 55 r / min and a temperature of 195° C.

[0069] Example 3

[0070] A corrosion-resistant insulating material for a street code protective cover comprises the following components in parts by weight: 77 parts of PVC, 27 parts of ABS, 11.3 parts of low-density polyethylene, 22 parts of modified fillers, 4.3 parts of stabilizers, 2.7 parts of lubricants, 1.3 parts of antioxidants and 0.9 parts of light stabilizers; the low-density polyethylene is Dow low-density polyethylene LDPE-740E; the stabilizer is formed by mixing zinc stearate and triphenyl phosphate in a mass ratio of 1:2.5; the lubricant is formed by mixing stearic acid and OPE wax in a mass ratio of 1:1; the antioxidant is formed by mixing antioxidant 1076, antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2:1.6; the light stabilizer is an ultraviolet absorber UV-326.

[0071] Wherein, the preparation method of the modified filler comprises the following steps:

[0072] S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles;

[0073] S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles;

[0074] S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

[0075] In step S1, the soaking condition is soaking at 45°C for 3.5 hours; the stirring and mixing is stirring at a speed of 2650r / min for 25 minutes; the washing is washing with deionized water until neutral; the drying is drying at 115°C for 3.5 hours; the calcination is calcining at 735°C for 2.5 hours; the mass ratio of the carbon fiber, sodium hydroxide aqueous solution, calcium chloride and deionized water is 3.4:9.3:1.7:53; the mass fraction of the ammonia water is 28%; the amount of ammonia water added is until no precipitation is produced;

[0076] In step S2, the stirring and dispersing is stirring at a speed of 560 r / min for 40 minutes; the heating and stirring is stirring at a temperature of 55° C. for 3.5 hours; the continued stirring is stirring at a temperature of 65° C. for 5.5 hours; the drying is drying at a temperature of 80° C. to constant weight; in step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 7:38:1.5:23; the silane coupling agent is silane coupling agent NQ-62; the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.47:4.3.

[0077] In step S3, the melt extrusion is carried out at a screw speed of 55 r / min and a temperature of 195° C.; the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 8.7:13:0.42; and the organic copolymer is styrene-glycidyl methacrylate copolymer.

[0078] A method for preparing a corrosion-resistant insulating material for a street code protective cover, the preparation method comprising the following steps:

[0079] Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix;

[0080] Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

[0081] In step 1, the stirring and mixing is performed at a temperature of 130° C. and a speed of 660 r / min for 25 min; the continued mixing is performed at a temperature of 130° C. and a speed of 1130 r / min for 25 min;

[0082] In step 2, the melt extrusion is carried out at a screw speed of 55 r / min and a temperature of 195° C.

[0083] Example 4

[0084] A corrosion-resistant insulating material for a street code protective cover comprises the following components in parts by weight: 80 parts of PVC, 30 parts of ABS, 12 parts of low-density polyethylene, 24 parts of modified fillers, 5 parts of stabilizers, 3 parts of lubricants, 1.5 parts of antioxidants and 1.0 parts of light stabilizers; the low-density polyethylene is Dow low-density polyethylene LDPE-740E; the stabilizer is formed by mixing zinc stearate and triphenyl phosphate in a mass ratio of 1:2.5; the lubricant is formed by mixing stearic acid and OPE wax in a mass ratio of 1:1; the antioxidant is formed by mixing antioxidant 1076, antioxidant 168 and antioxidant 1010 in a mass ratio of 1:2:1.6; the light stabilizer is an ultraviolet absorber UV-326.

[0085] Wherein, the preparation method of the modified filler comprises the following steps:

[0086] S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles;

[0087] S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles;

[0088] S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

[0089] In step S1, the soaking condition is soaking at 45°C for 4.0 hours; the stirring and mixing is stirring at a speed of 300r / min for 30 minutes; the washing is washing with deionized water until neutral; the drying is drying at 120°C for 4 hours; the calcination is calcining at 800°C for 3 hours; the mass ratio of the carbon fiber, sodium hydroxide aqueous solution, calcium chloride and deionized water is 3.6:10:1.8:60; the mass fraction of the ammonia water is 30%; the amount of ammonia water added is until no precipitation is generated;

[0090] In step S2, the stirring and dispersing is stirring at a speed of 600 r / min for 45 minutes; the heating and stirring is stirring at a temperature of 60° C. for 4 hours; the continued stirring is stirring at a temperature of 70° C. for 6 hours; the drying is drying at a temperature of 80° C. to constant weight; in step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 8:40:1.6:25; the silane coupling agent is silane coupling agent NQ-62; the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.48:4.5.

[0091] In step S3, the melt extrusion is carried out at a screw speed of 60 r / min and a temperature of 200° C.; the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 9:14:0.43; and the organic copolymer is styrene-glycidyl methacrylate copolymer.

[0092] A method for preparing a corrosion-resistant insulating material for a street code protective cover, the preparation method comprising the following steps:

[0093] Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix;

[0094] Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

[0095] In step 1, the stirring and mixing is performed at a temperature of 135° C. and a speed of 700 r / min for 30 min; the continued mixing is performed at a temperature of 135° C. and a speed of 1200 r / min for 30 min;

[0096] In step 2, the melt extrusion is carried out at a screw speed of 58 r / min and a temperature of 200° C.

[0097] Comparative Example 1

[0098] Compared with Example 3, the difference in Comparative Example 1 is that deionized water is used instead of the sodium hydroxide aqueous solution in step S1, and the other components, preparation steps and parameters are the same.

[0099] Comparative Example 2

[0100] Compared with Example 3, Comparative Example 2 is different in that calcium chloride is not used, and the remaining components, preparation steps and parameters are the same.

[0101] Comparative Example 3

[0102] Compared with Example 3, Comparative Example 3 is different in that silane coupling agent KH-560 is used instead of silane coupling agent NQ-62, and the other components, preparation steps and parameters are the same.

[0103] Comparative Example 4

[0104] Compared with Example 3, Comparative Example 4 is different in that vinyl triethoxysilane is used instead of the silane coupling agent NQ-62, and the other components, preparation steps and parameters are the same.

[0105] Comparative Example 5

[0106] Compared with Example 3, Comparative Example 5 is different in that salicylaldehyde is used instead of 5-fluorosalicylaldehyde, and the other components, preparation steps and parameters are the same.

[0107] Comparative Example 6

[0108] Compared with Example 3, Comparative Example 6 is different in that no organic copolymer is used, and the other components, preparation steps and parameters are the same.

[0109] The corrosion-resistant insulating materials prepared in Examples 1-4 and Comparative Examples 1-6 were tested as follows, and the test results are shown in Table 1.

[0110] Tensile strength test: refer to GB / T1040.2-2022, and conduct tensile strength test on samples at a tensile rate of 50 mm / min;

[0111] Corrosion resistance test: After weighing the sample, the acid treatment is to immerse it completely in 10wt% hydrochloric acid at 60℃ for 48h; the alkali treatment is to immerse it completely in 10wt% potassium hydroxide solution at 60℃ for 48h. After immersion, wash it with deionized water, dry it, weigh it, and calculate the weight loss rate.

[0112] Table 1

[0113] Tensile strength(MPa) Acid immersion weight loss rate (%) Alkali leaching weight loss rate (%) Example 1 52.4 0.72 0.64 Example 2 53.2 0.67 0.59 Example 3 53.8 0.61 0.54 Example 4 52.7 0.65 0.58 Comparative Example 1 44.5 3.64 2.86 Comparative Example 2 41.6 4.14 3.95 Comparative Example 3 38.7 6.03 5.68 Comparative Example 4 40.3 4.82 4.46 Comparative Example 5 46.7 4.28 3.75 Comparative Example 6 37.4 8.32 7.81

[0114] From the test results in Table 1, it can be seen that compared with comparative examples 1-6, the corrosion-resistant insulating materials prepared in Examples 1-4 of the present invention have excellent mechanical properties and also have good acid and alkali corrosion resistance. Through the analysis of Examples 1-4 and Comparative Examples 1-6 in combination with Table 1, it can be seen that the present invention uses sodium hydroxide to make the surface of the carbon fiber rough while introducing more active hydroxyl groups, and then generates calcium oxide particles on the surface of the carbon fiber to weaken the force between the carbon fiber molecules, reduce the self-agglomeration phenomenon, and at the same time, the calcium oxide can be evenly distributed on its surface. Then, the mixed particles are surface modified by a silane coupling agent to introduce more active functional groups so that it can graft 5-fluorosalicylaldehyde and form an imine bond chemical connection. The introduction of fluorine element increases its compatibility in the PVC / ABS system, and combined with the benzene ring structure on the salicylaldehyde phase, it can form a physical bond with the benzene ring structure of the organic copolymer, thereby improving the mechanical properties and the corrosion resistance. The silane coupling agent can also promote the formation of covalent bonds between the prefabricated particles and the organic copolymer, further improve the compatibility and dispersibility of the prefabricated particles in the PVC / ABS system, and further enhance the performance of the composite material. The organic copolymer is used as a compatibilizer and a reinforcing agent to improve the mechanical properties and corrosion resistance of the composite material.

[0115] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A corrosion-resistant insulating material for street code protective cover, It is characterized in that The following components are included by weight: 70-80 parts of PVC, 20-30 parts of ABS, 10-12 parts of low-density polyethylene, 18-24 parts of modified filler, 3-5 parts of stabilizer, 2-3 parts of lubricant, 1.0-1.5 parts of antioxidant and 0.6-1.0 parts of light stabilizer; The preparation method of the modified filler comprises the following steps: S1. Soak the carbon fiber in a sodium hydroxide aqueous solution, filter and take out the solid, wash, dry to constant weight, add calcium chloride and deionized water, stir and mix, add ammonia water for precipitation reaction, filter, wash, dry, and calcine to obtain mixed particles; S2, after the mixed particles and anhydrous ethanol are mixed and stirred and dispersed, a silane coupling agent is added, heated and stirred, filtered, an aromatic aldehyde solution is added, and stirring is continued, after filtering, a solid is taken out for washing and drying to obtain prefabricated particles; S3, melt-extruding and granulating the prefabricated particles, the organic copolymer and the initiator to obtain a modified filler.

2. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: The stabilizer is one or more of zinc stearate, magnesium stearate and triphenyl phosphate; the lubricant is one or more of stearic acid, polyethylene wax, glycerol stearate and OPE wax; the antioxidant is one or more of antioxidant 1076, antioxidant 626, antioxidant 168 and antioxidant 1010; the light stabilizer is one or more of ultraviolet absorber UV-326, ultraviolet absorber UV-327 and ultraviolet absorber UV-1130.

3. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: In step S1, the soaking condition is soaking at 40-45°C for 3.0-4.0h; the stirring and mixing is stirring at 200-300r / min for 20-30min; the washing is washing with deionized water until neutral; the drying is drying at 110-120°C for 3-4h; and the calcination is calcining at 600-800°C for 2-3h.

4. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: In step S1, the mass ratio of the carbon fiber, sodium hydroxide aqueous solution, calcium chloride and deionized water is 3.0-3.6:8-10:1.5-1.8:40-60; the mass fraction of the ammonia water is 25-30%; and the amount of ammonia water added is until no precipitation is generated.

5. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: In step S2, the stirring and dispersing is stirring at a speed of 500-600 r / min for 30-45 min; the heating and stirring is stirring at a temperature of 40-60° C. for 3-4 h; the continued stirring is stirring at a temperature of 60-70° C. for 5-6 h; and the drying is drying at a temperature of 80° C. to constant weight.

6. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: In step S2, the mass ratio of the mixed particles, anhydrous ethanol, silane coupling agent and aromatic aldehyde solution is 5-8:35-40:1.3-1.6:20-25; the silane coupling agent is silane coupling agent NQ-62; the aromatic aldehyde solution is prepared by mixing 5-fluorosalicylaldehyde and anhydrous ethanol in a mass ratio of 0.45-0.48:4.0-4.

5.

7. The corrosion-resistant insulating material for street code protective cover according to claim 1, Features: In step S3, the melt extrusion is carried out at a screw speed of 50-60 r / min and a temperature of 180-200°C; the mass ratio of the prefabricated particles, the organic copolymer and the initiator is 8-9:10-14:0.40-0.43; and the organic copolymer is styrene-glycidyl methacrylate copolymer.

8. A method for preparing the corrosion-resistant insulating material for street code protection cover according to any one of claims 1 to 7, It is characterized in that The preparation method comprises the following steps: Step 1: Stir and mix PVC, ABS and low-density polyethylene in an internal mixer, add modified filler, stabilizer, lubricant, antioxidant and light stabilizer and continue mixing to obtain a premix; Step 2: placing the premix in a twin-screw extruder for melt extrusion and granulation to obtain a corrosion-resistant insulating material.

9. The method for preparing the corrosion-resistant insulating material for the street code protective cover according to claim 8, Features: In step 1, the stirring and mixing is performed at a temperature of 120-135°C and a rotation speed of 600-700 r / min for 20-30 min; and the continued mixing is performed at a temperature of 120-135°C.

Citation Information

Patent Citations

  • Preparation process of high-modified wear-resistant PVC (polyvinyl chloride) material cable sheath

    CN114479310A

  • Luminescent high-performance PVC optical cable material and preparation method thereof

    CN114933764A